2012
DOI: 10.1007/s10825-012-0387-x
|View full text |Cite
|
Sign up to set email alerts
|

Coupled electro-thermal simulation of MOSFETs

Abstract: Thermal transport in metal-oxide-semiconductor field effect transistors (MOSFETs) due to electron-phonon scattering is simulated using phonon generation rates obtained from an electron Monte Carlo device simulation. The device simulation accounts for a full band description of both electrons and phonons considering 22 types of electron-phonon scattering events. Detailed profiles of phonon emission/absorption rates in the physical and momentum spaces are generated and are used in a MOS-FET thermal transport sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Previously, it was reported that the peak temperature of the FDSOI devices is located close to the drain end of the device [1], [7] and the peak temperature value in FDSOI FETs is found to be much higher than the one in the conventional bulk MOSFETs [8]. The higher peak temperature of the FDSOI structure is mainly due to the thermal behaviour of its constitutive materials.…”
Section: Introductionmentioning
confidence: 93%
“…Previously, it was reported that the peak temperature of the FDSOI devices is located close to the drain end of the device [1], [7] and the peak temperature value in FDSOI FETs is found to be much higher than the one in the conventional bulk MOSFETs [8]. The higher peak temperature of the FDSOI structure is mainly due to the thermal behaviour of its constitutive materials.…”
Section: Introductionmentioning
confidence: 93%
“…The consequence is having a longer conduction time. Since the PO and PI devices are ON for longer durations when compared to the other groups, they have higher average power density values according to (12) and they become the most critical devices in terms of creating a hotspot.…”
Section: Self-heating Of Devices With Different Functionsmentioning
confidence: 99%
“…Previously, it was reported that the peak temperature of the FDSOI devices is located close to the drain end of the device [1,10,11] and the peak temperature value in FDSOI FETs is found to be much higher than the one in the conventional bulk MOSFETs [12,13]. The higher peak temperature of the FDSOI structure is mainly due to the thermal behaviour of its constitutive materials.…”
Section: Introductionmentioning
confidence: 95%
“…15 Hatakeyama and Fushinobu 17 employed a similar model to study the thermal cross-talk between the nMOS and pMOS FETs of 90 nm channel length that were set side-by-side to design a CMOS gate. Although these approaches-strongly efficient in terms of computational resources-capture some aspects of the out equilibrium energy transfers that are involved in sub-micron devices, they are not suitable to provide a deep microscopic insight of phonon transport 18 19 They simulated a simple 1D n-i-n Si device. However, the contribution of optical phonons was neglected.…”
Section: Introductionmentioning
confidence: 99%